My way to Islam - Philips, Abu Ameenah Bilal; One Islam Productions (N.S.W, Australia : One Islam Productions, 2006)
This is an inspiring account of one man's search for the true meaning of life, and how he chose Islam at the end of his journey. Another insight into why Islam is the fastest growing religion in the world
Title from title screen
Presenter : Bilal Philips
Keywords: Islam -- Customs and practices; Religious life -- Islam